Normoxic and Hyperoxic Cardiopulmonary Bypass in Congenital Heart Disease. (18th September 2014) - Mokhtari, Amir; Lewis, Martin
Abstract : Cyanotic congenital heart disease comprises a diverse spectrum of anatomical pathologies. Common to all, however, is chronic hypoxia before these lesions are operated upon when cardiopulmonary bypass is initiated. A range of functional and structural adaptations take place in the chronically hypoxic heart, which, whilst protective in the hypoxic state, are deleterious when the availability of oxygen to the myocardium is suddenly improved. Conventional cardiopulmonary bypass delivers hyperoxic perfusion to the myocardium and is associated with cardiac injury and systemic stress, whilst a normoxic perfusate protects against these insults.